Pengaruh Return on Assets, Equity dan Earning Per Share Terhadap Harga Saham Sektor Perbankan di Bursa Efek Indonesia - Cindy Halim Putri; Tina Lestari; Noor Ritawaty (Owner : Riset dan Jurnal Akuntansi, 2022)
Capital markets can help companies in providing funds for companies. Investors will invest in the capital market in hopes of gaining profits. Investors in investing their capital will see financial performance in the form of financial ratios as a consideration in investing their capital. The purpose of this study is to determine the effect of Return on Assets (ROA), Return on Equity (ROE) and Earning Per Share (EPS) variables on stock prices in banking companies on the Indonesia Stock Exchange. The population used in this study is banking industry listed on the Indonesia Stock Exchange as many as 43 companies. While the sample used in this study were 9 companies. The research method in this study is quantitative correlation. This study uses the Classic Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing. The results of this study indicate that Return on Assets (ROA) has no significant effect on stock prices, Return on Equity (ROE) has a significant effect on stock prices, and Earning Per Share (EPS) has a significant effect on stock prices. Overall, the variables in this study affect the stock price. Meanwhile, it is known that Return on Equity (ROE) has the most dominant influence on stock prices.